ВЗАИМОСВЯЗИ ДИАСТОЛИЧЕСКОЙ ФУНКЦИИ ЛЕВОГО ЖЕЛУДОЧКА С ЕГО МОРФОФУНКЦИОНАЛЬНЫМИ ОСОБЕННОСТЯМИ, ПОКАЗАТЕЛЯМИ ПЕРИФЕРИЧЕСКОЙ ГЕМОДИНАМИКИ И ДАННЫМИ СУТОЧНОГО МОНИТОРИРОВАНИЯ АРТЕРИАЛЬНОГО ДАВЛЕНИЯ У ПАЦИЕНТОВ С АРТЕРИАЛЬНОЙ ГИПЕРТЕНЗИЕЙ - С. В. Самоявчева; Е. В. Гурвич; В. В. Шкарин (SINAPS LLC, 2014)
Various disorders of the diastolic function of left ventricle are formed due to concentric and eccentric types of hypertrophy. The processes of elevation of myocardial stiffness and reduction of lard-bore arterial vessel elastance develop parallel and at the early stages are accompanied with the rise of isolated systolic hypertension frequency, at the later stages - isolated systolic and systolic-diastolic arterial hypertension.